Developing translational bioethics—Suggestions for ways forward - Frith, Lucy (Bioethics, 2024)
This paper will take as its starting point the premise that developing translational bioethics is a worthwhile endeavour. I will develop an account of translational bioethics and discuss what implications this would have for the wider discipline of bioethics and argue that this would be a useful development for bioethics. The paper will conduct a form of ‘translational meta-bioethics analysis’, in the words of Bærøe. I will argue that if we are serious about instituting translational bioethics, then it will need to look and be organised in a very different way from current bioethics research, this will be a radically different form of bioethics from what we currently have. In this paper I will sketch what translational bioethics might look like. My proposal here is not that translational bioethics should supplant existing ways of doing bioethics, but rather that it should be an addition to it, another subdiscipline of bioethics.